Pendidikan Pesantren dalam Menghadapi Tantangan Radikalisme - Abdul Halim (FALASIFA : Jurnal Studi Keislaman, 2017)
Pesantren educational institution is one of the containers, who participate in educating and participating in building the nation. Pondok pesantren who in p apply the principle hablum minallah (relationship with God), hablum minannas and hablum minalnas. The role of pesantren education is very strategic in preventing the existence of religious radicalism. Which is the phenomenon of radicalism that happened to lead to violence. the possibility of such events will continue to be a threat as well as a challenge for the world of boarding schools as well as challenges for the religions in Indonesia in general. Growing anti-violence religion with all the values of the wisdom of pesantren education, perhaps is an attempt to build anormative theological awareness as well as social consciousness,in which we live in a complex society with existing problems and plural society in terms of religion, culture, ethnicity of its various social diversity. Keywords: Pendidikan, Pesantren, Radikalisme